Influence of microwave heating time on the structure and properties of chitosan films. Issue 18 (19th April 2014) - Jacquot, Charlotte; Jacquot, Muriel; Marques, Patrícia; Jasniewski, Jordane; Akhtar, Muhammad Javeed; Didelot, Anne‐Sophie; Desobry, Stéphane
ABSTRACT: The aim of this study was to investigate chitosan film behavior during microwave heating for 10 different heating times from 0 to 40 min. Chitosan films were produced by casting. Their structure and properties were investigated with several techniques, including Fourier transform infrared spectroscopy and differential scanning calorimetry, but also by the measurement of the film color and the mechanical properties or by the study of the rheological properties of the rehydrated films. An original technique of gas chromatography (electronic nose) was used to analyze the film odor and highlight the presence of volatile compounds related to the Maillard reaction occurring during film heating. The results show that structural modifications occurred in two steps; this affected the polymer structure, such as the crystallization and chain scission. The appearance of the neoformed compounds was also observed and must be controlled to guarantee the safety of this food‐contact packaging material. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2014, 131, 40779. Abstract :